A compact cognitive radio UWB/reconfigurable antenna system with controllable communicating antenna bandwidth. Issue 1 (2nd January 2019) - Abdulhameed, Abdulghafor Abdulghafar; Alnahwi, Falih Mahdi; Swadi, Husham Lateef; Abdullah, Abdulkareem Swadi
ABSTRACT: A low profile and compact size cognitive radio (CR) sensing/communicating antenna system is presented in this paper. A slotted elliptical monopole antenna is proposed as an ultra-wideband sensing antenna for the CR system, while the CR communication relies on a triangular reconfigurable monopole antenna. Two PIN diodes are attached to the reconfigurable antenna to provide four different wideband CR communications with variable bandwidths. The simulation and measured results are in good agreement, and they demonstrate that both antennas have an omnidirectional radiation pattern with acceptable gain values compatible with the portable CR devices. In addition, the results show low mutual coupling between the sensing antenna and the communicating antenna that reaches to values less than −16 dB for all operational modes of the PIN diodes.